The Role of Cold Inducible RNA-Binding Protein in Cardiac Physiology and Diseases - Zhong, Peng; Peng, Jianye; Bian, Zhouyan; Huang, He (Frontiers in Pharmacology, 2021)
Cold-inducible RNA-binding protein (CIRP) was is an intracellular stress-response protein, which can respond to a variety of stress conditions by changing its expression and regulating mRNA stability. As an RNA-binding protein, CIRP has been described to modulate gene expression at the post-transcriptional level, including those involved in DNA repair, cellular redox metabolism, circadian rhythms, telomere maintenance, and cell survival. CIRP is expressed in a large variety of tissues, including the testis, brain, lung, kidney, liver, stomach, bone marrow, and heart. Recent studies implicated an important role of CIRP in cardiac physiology and diseases. CIRP has been demonstrated to regulate cardiac electrophysiological properties such as the repolarization of cardiomyocytes, the susceptibility of atrial fibrillation, and the function of the sinoatrial node in response to stress. In addition, CIRP has also been suggested to protect cardiomyocytes from apoptosis under various stress conditions including heart failure, high glucose conditions, as well as during extended heart preservation under hypothermic conditions. Here, we summarized the findings of CIRP investigation in cardiac physiology and diseases and the underlying molecular mechanisms.